Development of a specific isothermal nucleic acid amplification for the rapid and sensitive detection of shrimp allergens in processed food. (1st December 2020) - Sheu, Shyang-Chwen; Yu, Min-Tse; Lien, Yi-Yang; Lee, Meng-Shiou
Highlights: A highly specific LAMP primer for the detection of shrimp DNA was developed. The sensitivity of LAMP was better than that of conventional PCR for shrimp DNA detection. Other Crustacea mixed with 0.01% shrimp did not interfere with the detection effectiveness of the LAMP assay. Shrimp products were identified by LAMP in various processed commercial foods. The developed LAMP assay can detect ingredients containing shrimp DNA and verify shrimp in commercial products. Abstract: Food allergens that cause anaphylactic reactions have become an important health problem worldwide. Among them, shrimp is a popular seafood in many cuisines. The best way to avoid allergic reactions is to mitigate the intake of food allergens. In this study, a loop-mediated isothermal amplification (LAMP) assay was developed for the detection of shrimp DNA. Using LAMP primers, the identification of shrimp DNA by the LAMP assay was specific and rapid (within 30 min). It exhibited no cross-reaction with the DNA of other Crustacea, including crabs and lobster, and at least 0.01% shrimp DNA existed in the test sample. Additionally, the sensitivity of LAMP for detecting shrimp DNA was 100-fold greater than that of conventional PCR. LAMP for the detection of shrimp DNA was reproducible regardless of whether the genomic DNA was extracted from boiled, steamed or roasted shrimp samples. In summary, the LAMP assay established herein not only could be potentially used for diagnosing shrimp DNA but could also be applicable for identifying shrimp allergens in commercial food products in marketplaces.